Prevalence of TB suspects, sputum positive TB cases and health seeking behaviour of TB suspects in a coastal ward Thiruvananthapuram corporation, Kerala - S., Mini S.; U., Anuja; ., Rajkafoor (International Journal Of Community Medicine And Public Health, 2017)
Background: The present study was conducted to estimate the prevalence of TB suspects and prevalence of sputum positive TB cases and health seeking behaviour of TB suspects in a coastal ward. Methods: The study was done as a cross sectional house to house survey. The study population was initially screened by a case definition and TB suspects were identified and details about their health seeking behaviour was collected using a structured questionnaire and two sputum samples (one spot and one early morning sample) also were collected for sputum microscopy. Results: The population screened using the case definition was 5466 (86% of total population above 15 years of age) and among this 131 (2.39%) was identified as TB suspects. Among the TB suspects 46.6% were males, 19.8% were diabetic, and 60.3% were having coughed more than 4 weeks. Prevalence of sputum positivity among the TB suspects was 13.1% and in the total study population was0.183%. About the health seeking behaviour only 65.65% have consulted a doctor. Among those consulted doctor, 46.5% were males, 93% have consulted an allopathic doctor and 46.52 have completed the prescribed treatment. Conclusions: The prevalence of TB suspects and sputum positive TB cases is high in this coastal ward and health seeking behaviour of Tb suspects is also very poor. This emphasizes the need for further improvement in case detection and IEC activities about Tuberculosis.